(untitled) (LEARNing Landscapes, 2011)
The inquiries of professionals involved in the development of a centre for inquiry into educational practice in a secondary school are fostered through professional conversation among teachers, support and professional staff undertaking research on practice. A framework for the development of the work done in the centre is briefly reviewed. Snapshots of various experiences and products illustrate evolving understandings of inquiry and evidence of ways in which it supports student learning and developing teaching practices in light of local curricular reforms.